Kelemahan Perlindungan HKI di Indonesia Berdasarkan Undang-Undang tentang Merek dan Indikasi Geografis - Nadhila Adani; Budi Santoso (Magister Kenotariatan Universitas Diponegoro, 2023)
AbstractIn recent years, intellectual property rights have developed prominently and have become a main topic of conversation, both nationally and internationally. So that the protection of intellectual property rights through registration becomes absolute. However, even though it has been registered in practice, there are still many counterfeits in the name of a brand, especially a well-known brand, it must be admitted that currently the illegal use of certain marks is still happening. Moreover, it is supported by the weaknesses contained in the legislation regarding, intellectual property rights itself, which tends to open a loophole for infringing intellectual property rights. The problem that will be discussed is, what are the weaknesses of the protection of intellectual property rights in Indonesia. In this study, the author uses a normative type by focusing on literature review. From the results of the study, it can be seen that the concept of the first registrant in trademark legislation creates a gap for irresponsible parties to register an international mark first in Indonesia, then there is a difference in the definition of the three-dimensional form between trademark legislation and desain legislation so that they collide with each other.Keywords: weaknesses; protection; intellectual property rightsAbstrakDalam beberapa tahun terakhir, hak kekayaan intelektual, termasuk paten mengalami perkembangan menonjol serta menjadi perbincangan hangat, baik secara nasional maupun dunia internasional. Sehingga perlindungan hak kekayaan intelektual melalui pendaftaran menjadi hal mutlak. Namun, meski telah didaftarkan dalam prakteknya masih banyak di temui berbagai tiruan yang mengatasnamakan suatu merek khususnya merek terkenal, harus diakui bahwa memang saat ini penggunaan merek tertentu secara illegal masih terus terjadi. Terlebih di dukung dengan kelemahan yang terdapat dalam peraturan perundangan mengenai HKI itu sendiri, yang cenderung membuka celah untuk melakukan pelanggaran atas hak kekayaan intelektual. Permasalahan yang akan di bahas adalah, bagaimanakah kelemahan perlindungan hak kekayaan intelektual di indonesia. Dalam penelitian ini penulis menggunakan jenis normatif dengan memfokuskan pada kajian kepustakaan. Dari hasil penelitian terlihat bahwa konsep pendaftar pertama dalam peraturan perundangan merek, memunculkan celah bagi pihak yang tidak bertanggung jawab untuk mendaftarkan merek internasional terlebih dahulu di Indonesia, kemudian terjadi perbedaan definisi tentang bentuk tiga dimensi antara peraturan perundangan merek dan perundangan desain sehingga saling bertabrakan. Kata kunci: kelemahan; perlindungan; hak kekayaan interlektual